Synthesis and Characterization of Carbon Dots (C-Dots) Derived from Tofu Dregs using Solvothermal Method - Siti Nurhalimah; Anggi Khairina Hanum Hasibuan; Yusuf Bramastya Apriliyanto; Heriyandi Heriyandi; Bagas Putra Arfyansyah (Universitas Nusa Cendana, 2026)
Tofu dregs are an agroindustrial organic byproduct generated in large quantities and still contain carbon-rich compounds such as carbohydrates, proteins, and lipids. This carbon content makes tofu dregs a promising alternative precursor for the synthesis of value-added carbon-based materials, one of which is carbon dots (C-Dots). This study aims to synthesize C-Dots derived from tofu dregs using a solvothermal method and to characterize the optical properties, functional groups, morphology, and elemental composition of the resulting material. The synthesis of C-Dots was carried out using a solvothermal process involving heating in a closed system using tofu dregs and 96% ethanol as the solvent. Characterization was performed using UV–Visible (UV–Vis) spectrophotometry, Fourier Transform Infrared–Attenuated Total Reflectance (FTIR–ATR), and Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (SEM–EDX). The UV–Vis analysis revealed an absorption band at approximately 451 nm, which is associated with π→π* electronic transitions in conjugated carbon structures, as well as a shoulder around 524 nm that can be attributed to n→π* transitions originating from lone pair electrons in oxygen-containing functional groups. FTIR analysis indicated the presence of O–H/N–H, C–H, C=C, C–O/C–O–C, and C–N functional groups on the surface of the C-Dots. Meanwhile, SEM analysis showed agglomerated particle morphology, and EDX results confirmed that the main constituent elements of the material are carbon (C), oxygen (O), and nitrogen (N). The results of this study demonstrate that tofu dregs have strong potential to be utilized as a biomass-derived precursor in the solvothermal synthesis of C-Dots.